Why Mergers Reduce Profits, and Raise Share Prices - Sven-Olof Fridolfsson; Johan Stennek (The Research Institute of Industrial Economics (IUI), 1999)
We demonstrate a 'preemptive merger mechanism' which may explain the empirical puzzle why mergers reduce profits, and raise share prices. A merger may confer strong negative externalilties on the firms outside the merger. If being an 'insider' is better than being an 'outsider', firms may merge to preempt their partner merging with someone else. Furthermore, the pre-merger value of a merging firm is low, since it reflects the risk of becoming an outsider. These results are derived in a model of endogenous mergers which predicts the conditions under which a merger occurs, when it occurs, and how the surplus is divided.
Keywords: C78; G34; L13; 330; Mergers & acquisitions; definsive merger; coalition formation; antitrust policy; Übernahme; Fusion; Wettbewerbsstrategie; Spieltheorie; Verhandlungstheorie; Theorie